2021
DOI: 10.1101/2021.05.26.21257794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultra-rare and common genetic variant analysis converge to implicate negative selection and neuronal processes in the aetiology of schizophrenia

Abstract: Both common and rare genetic variants (minor allele frequency > 1% and < 0.1% respectively) have been implicated in the aetiology of schizophrenia. In this study, we integrate single-cell gene expression data with publicly available Genome-Wide Association Study (GWAS) and exome sequenced data in order to investigate in parallel, the enrichment of common and (ultra-)rare variants related to schizophrenia in several functionally relevant gene sets. Four types of gene sets were constructed 1) protein-trunc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In schizophrenia, well-powered datasets on both common and rare variants have allowed for a more comprehensive mechanistic interrogation, with emerging biological convergence across both ends of the allelic frequency spectrum 64,106,111,138 . Both rare and common variant associations with schizophrenia have strongly implicated genes influencing synaptic organization, differentiation and signaling, at both presynaptic and postsynaptic locations 64,106,139 .…”
Section: Emerging Biological Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…In schizophrenia, well-powered datasets on both common and rare variants have allowed for a more comprehensive mechanistic interrogation, with emerging biological convergence across both ends of the allelic frequency spectrum 64,106,111,138 . Both rare and common variant associations with schizophrenia have strongly implicated genes influencing synaptic organization, differentiation and signaling, at both presynaptic and postsynaptic locations 64,106,139 .…”
Section: Emerging Biological Insightsmentioning
confidence: 99%
“…The evolutionary constrained genes have a high probability of being intolerant to loss‐of‐function mutations, and are relatively depleted of equivalent protein‐disrupting variants in the general population 110 . Recently, such genes have also been implicated by common variant findings for schizophrenia 111 .…”
Section: Rare Variantsmentioning
confidence: 99%
“…Unlike other literature, this study did not use sequence or exome array data due to a lack of availability for large symptomlevel data, but the UK Biobank Axiom array also covers variation in exonic regions and areas of rare coding variation including protein-truncating variants [78]. The lower coverage of these genomic regions means the results of this study are not informative about the contribution of ultra-rare, de novo and private mutations, which have been implicated in previous studies of psychiatric illness [11,15,79].…”
Section: Enrichment Of Genes Identified By Gwasmentioning
confidence: 99%
“…In psychiatry, few studies have focused on rare genetic variants associated with major depression [9,10], while several have investigated schizophrenia and bipolar disorder [11][12][13]. Studies of some psychiatric disorders including schizophrenia have found an enrichment of ultra-rare disruptive variants [11,14,15] and studies of common variants for complex diseases have found enrichment of genes associated with matched Mendelian disorders [16].…”
Section: Introductionmentioning
confidence: 99%